Higher education strategies for enhancing employability of international students: A systematic review in the post-pandemic era - Xu, Sha; Mansor, Azlin Norhaini; Amat, Salleh (Journal of International Students, 2025)
This study investigates the role of higher education strategies in enhancing the employability of international students in the postpandemic era, employing the USEM (understanding, skills, efficacy beliefs, metacognition) as a theoretical framework. By focusing on targeted interventions, this research explores how higher education institutions address key employability dimensions to support students’ academic, professional, and personal development. Using a systematic literature review approach guided by the PRISMA framework, the study included 23 publications from 2020–2024. The findings highlight the effectiveness of strategies such as culturally responsive reflective practices, work-integrated learning (WIL), tailored career support, and curriculum-embedded skill development. These approaches enhance students’ abilities, equipping them with the ability to succeed in competitive and diverse labor markets. By providing actionable insights, this research enriches the understanding of employability strategies within the USEM framework and offers valuable recommendations for institutions and policymakers to design culturally inclusive, evidence-based career interventions.